Spinal Diffuse Midline Glioma H3 K27M -Altered: Report of a Rare Tumor with Extracranial Skeletal Metastases and Review of Literature - Rathi, Aditi; Choudhari, Amit Kumar; Chatterjee, Abhishek; Sahay, Ayushi; Bhattacharya, Kajari; Sahu, Arpita; Puranik, Ameya D; Shah, Aekta; Dasgupta, Archya; Gupta, Tejpal; Epari, Sridhar (International journal of surgical pathology, 2025)
Diffuse midline glioma, -altered is a rare and aggressive pediatric brain tumor with a grim prognosis. Diffuse midline glioma is characterized by specific molecular alterations, including mutations, and involves deep midline structures such as the brainstem, cerebellum, spinal cord, and thalamus. These tumors present with a classic triad of symptoms and have limited surgical options due to their challenging locations. Extra-neural metastases are an unusual occurrence in diffuse midline glioma and have been rarely described. Here we report a 17-year-old girl with spinal diffuse midline glioma, who presented with multiple metastatic osseous lesions confirmed on biopsy of the thoracic vertebral lesion. Due to the rapid disease progression, the patient was recommended palliative therapy. Extra-neural metastases in diffuse midline glioma are rare, with only 16 reported patients, and no standard therapy exists. An accurate and early diagnosis is necessary to develop a personalized plan of treatment. Further research is needed to gain insights into the molecular pathology of diffuse midline glioma, -altered, and improve the quality of life and the outcome of patients with this deadly disease.